Konsep Pengembangan Kurikulum - Mohamad Mustafid Hamdi (Intizam, Jurnal Manajemen Pendidikan Islam, 2017)
The curriculum is a level of instructional material developed using the philosophy of progressivism as its main foundation, so the educational objectives are more directed at the process of developing and self-actualizing students and more oriented towards the development of affective aspects. Curriculum development using the philosophy of reconstructivism as its main basis, the educational objectives are directed at efforts to solve crucial social problems and the ability to work together. While the curriculum is developed using the basis of the philosophy of educational technology and the theory of technological education, the goal of education is more directed towards the achievement of competence . In implementing the analysis of components about educational curriculum development is a very complex challenge, it can be said that it is almost impossible to formulate curriculum objectives by only adhering to one philosophy, educational theory or a particular curriculum model consistently and consequently. Therefore, to accommodate the challenges and educational needs that are very complex, an eclectic model is often used, taking the best and most possible things from all the existing philosophical streams, so that in determining the educational objectives it is more balanced.